Global, Regional, and National Levels and Trends in Maternal Mortality Between 1990 and 2015, With Scenario-based Projections to 2030: A Systematic Analysis by the UN Maternal Mortality Estimation Inter-Agency Group. Issue 4 (December 2016) - Alkema, Leontine; Chou, Doris; Hogan, Daniel; Zhang, Sanqian; Moller, Ann-Beth; Gemmill, Alison; Fat, Doris Ma; Boerma, Ties; Temmerman, Marleen; Mathers, Colin; Say, Lale
Abstract : ( Lancet 2016;387: 462–674) World leaders at the landmark Millennium Summit in September 2000 agreed to adopt the Millennium Development Goals (MDGs) with the goal of improving the lives of the world's poor. Countries and international agencies agreed to monitor progress on these goals that addressed development and health outcomes between 1990 and 2015. One of the goals, MDG 5, strived for a reduction of 75% in the world-wide maternal mortality ratio over these 25 years. The objective of this current study was to project the levels and trends in maternal mortality for 183 countries for the period 2016 to 2030 based on the data obtained for MDG 5.